Shared Grasping: a Combination of Telepresence and Grasp Planning - Hertkorn, Katharina (KIT Scientific Publishing, 2016)
''Shared Grasping'' describes a new approach to shared autonomy for grasping and manipulation tasks to be used in a telepresence system. It is realized with two assistance functionalities, which simplify the grasping, and a user interface, which merges haptic feedback and visual assistance. User studies confirm a reduction in operator workload and an increase in task performance while maintaining a high immersion of the operator into the remote environment when using the assistance functions.